Cathelicidin-3 Associated With Serum Extracellular Vesicles Enables Early Diagnosis of a Transmissible Cancer - Espejo, Camila; Wilson, Richard; Pye, Ruth J.; Ratcliffe, Julian C.; Ruiz-Aravena, Manuel; Willms, Eduard; Wolfe, Barrett W.; Hamede, Rodrigo; Hill, Andrew F.; Jones, Menna E.; Woods, Gregory M.; Lyons, A. Bruce (Frontiers in Immunology, 2022)
The identification of practical early diagnostic biomarkers is a cornerstone of improved prevention and treatment of cancers. Such a case is devil facial tumor disease (DFTD), a highly lethal transmissible cancer afflicting virtually an entire species, the Tasmanian devil (Sarcophilus harrisii). Despite a latent period that can exceed one year, to date DFTD diagnosis requires visual identification of tumor lesions. To enable earlier diagnosis, which is essential for the implementation of effective conservation strategies, we analyzed the extracellular vesicle (EV) proteome of 87 Tasmanian devil serum samples using data-independent acquisition mass spectrometry approaches. The antimicrobial peptide cathelicidin-3 (CATH3), released by innate immune cells, was enriched in serum EVs of both devils with clinical DFTD (87.9% sensitivity and 94.1% specificity) and devils with latent infection (i.e., collected while overtly healthy, but 3-6 months before subsequent DFTD diagnosis; 93.8% sensitivity and 94.1% specificity). Although high expression of antimicrobial peptides has been mostly related to inflammatory diseases, our results suggest that they can be also used as accurate cancer biomarkers, suggesting a mechanistic role in tumorous processes. This EV-based approach to biomarker discovery is directly applicable to improving understanding and diagnosis of a broad range of diseases in other species, and these findings directly enhance the capacity of conservation strategies to ensure the viability of the imperiled Tasmanian devil population.